The Effect of Heat Flux on the Frequency of Bubble Appearance in a Boiling Pool - Muhammad Hasan; Supriyadi; Larasati Rizky Putri; Sofia Debi Puspa; Sentot Novianto (Fakultas Teknik Universitas Pancasila, 2024)
This research was conducted to determine the effect of heat flux on the frequency of bubbles appearing in boiling ponds. All fluid movement in pool boiling is caused by natural convection currents. The boiling pool consists of four areas of the pool boiling regime. The division of the four areas is based on the value of the heat flux and the difference between the surface temperature of the heater and the fluid. Using a two-phase heat transfer unit (H654 P.A. Hilton machine), The results showed that the power used greatly influences the boiling process, and besides that, the volume of water used also affects the duration of the boiling process. Based on tests using various power levels of 75 W, 110 W, 168 W, 237.5 W, and 290 W. The occurrence of bubbles will be faster and more numerous when using a lower volume of water and greater power. The heat transfer will be greater if a bubble appears, where latent heat plays a very important role. With mathematical analysis, an increase of 1 bubble per minute occurs for every increase in heat flux of 1.3 W/m2.